Postpartum-Specific Vital Sign Reference Ranges. Issue 2 (February 2021) - Green, Lauren J.; Pullon, Rebecca; Mackillop, Lucy H.; Gerry, Stephen; Birks, Jacqueline; Salvi, Dario; Davidson, Shaun; Loerup, Lise; Tarassenko, Lionel; Mossop, Jude; Edwards, Clare; Gauntlett, Rupert; et al.
Abstract : OBJECTIVE: To estimate normal ranges for postpartum maternal vital signs. METHODS: We conducted a multicenter prospective longitudinal cohort study in the United Kingdom. We recruited women before 20 weeks of gestation without significant comorbidities and with accurately dated singleton pregnancies. Women recorded their own blood pressure, heart rate, oxygen saturation and temperature daily for 2 weeks postpartum. Trained midwives measured participants' vital signs including respiratory rate around postpartum days 1, 7, and 14. RESULTS: From August 2012 to September 2016, we screened 4, 279 pregnant women; 1, 054 met eligibility criteria and chose to take part. Postpartum vital sign data were available for 909 women (86.2%). Median, or 50th centile (3rd–97th centile), systolic and diastolic blood pressures increased from the day of birth: 116 mm Hg (88–147) and 74 mm Hg (59–93) to a maximum median of 121 mm Hg (102–143) and 79 mm Hg (63–94) on days 5 and 6 postpartum, respectively, an increase of 5 mm Hg (95% CI 3–7) and 5 mm Hg (95% CI 4–6), respectively. Median (3rd–97th centile) systolic and diastolic blood pressure returned to 116 mm Hg (98–137) and 75 mm Hg (61–91) by day 14 postpartum. The median (3rd–97th centile) heart rate was highest on the day of birth, 84 beats per minute (bpm) (59–110) decreasing to a minimum of 75 bpm (55–101) 14 days postpartum. Oxygen saturation, respiratory rate, and temperature did not change in the 2 weeks postbirth. Median (3rd–97th centile) day-of-birth oxygen saturation was 96% (93–98). Median (3rd–97th centile) day-of-birth respiratory rate was 15 breaths per minute (10–22). Median (3rd–97th centile) day-of-birth temperature was 36.7°C (35.6–37.6). CONCLUSION: We present widely relevant, postpartum, day-specific reference ranges which may facilitate early detection of abnormal blood pressure, heart rate, respiratory rate, oxygen saturation and temperature during the puerperium. Our findings could inform construction of an evidence-based modified obstetric early warning system to better identify unwell postpartum women. CLINICAL TRIAL REGISTRATION: ISRCTN, 10838017. Abstract : Postpartum-specific reference ranges for blood pressure, heart rate, respiratory rate, oxygen saturation, and temperature may facilitate early identification of unwell postpartum women.